Fatty acid-binding protein gene is indispensable for molting process in Heortia vitessoides (Lepidoptera: Crambidae) - Qing-ya YE; Zhi-xing LI; Qing-ling CHEN; Ming-xu SUN; Ming-liang YIN; Tong LIN (Journal of Integrative Agriculture, 2023)
As intracellular fatty acid (FA) carriers, FA-binding proteins (FABPs) widely participate in the absorption, transport, and metabolism of FAs. It is a key protein in insect lipid metabolism and plays an important role in various physiological activities of insects. An FABP gene (HvFABP) was cloned from the transcriptional library of Heortia vitessoides Moore (Lepidoptera: Crambidae), and its expression patterns were determined using reverse transcription quantitative PCR (RT-qPCR). Stage- and tissue-specific expression profiles indicated that HvFABP highly expressed from prepupal to adult stages and in larval midgut and adult wings. HvFABP expression may be induced through starvation, mRNA expression was downregulated at 24 and 48 h and upregulated at 72 h after starvation. Furthermore, 20-hydroxyecdysone can induce the upregulation of its expression. RNA interference-mediated silencing of HvFABP significantly inhibited HvFABP expression, resulting in delayed development, abnormal molting or lethal phenotypes, and a significantly reduced survival rate. These results indicate that HvFABP plays a key role in the molting of H. vitessoides.